Carcinoembryonic antigen levels in pancreatic juice are associated with histological subtypes of intraductal papillary mucinous neoplasm of the pancreas - Hiroshi Hayakawa; Mitsuharu Fukasawa; Shinichi Takano; Hiroko Shindo; Ei Takahashi; Satoshi Kawakami; Yoshimitsu Fukasawa; Natsuhiko Kuratomi; Tadashi Sato; Makoto Kadokura; Sumio Hirose; Shinya Maekawa; et al. (DEN Open)
Abstract Background The present study aimed to examine the correlation between preoperative carcinoembryonic antigen levels in pancreatic juice (PJ‐CEA) and the histological subtype of intraductal papillary mucinous neoplasm (IPMN). Methods We enrolled IPMN patients who underwent endoscopic retrograde pancreatography between March 2002 and March 2018. Clinical factors associated with IPMN histological subtypes of 67 patients who underwent surgery were analyzed. Furthermore, the relationship between CEA immunohistochemistry findings and histological subtypes was investigated. Results Median PJ‐CEA were 15 ng/ml in the gastric type, 150 ng/ml in the intestinal type, and 175 ng/ml in the pancreatobiliary type. Both intestinal and pancreatobiliary types had significantly higher PJ‐CEA than the gastric type (p = 0.001). In the analysis of histological subtype predictors, high PJ‐CEA (≥63 ng/ml) only showed a significant difference in multivariate analyses (95% confidence interval 4.8–70.2; p < 0.001). Immunohistochemistry findings revealed significantly higher CEA expression in the non‐gastric type than in the gastric type (p < 0.001). The non‐gastric type showed a significantly worse prognosis than the gastric type (p = 0.017). Conclusion PJ‐CEA was an independent predictor of IPMN histological subtypes in a preoperative setting. High PJ‐CEA predict the non‐gastric type, while low PJ‐CEA predict the gastric type.